Public Digital Public Relations Melalui Media Sosial Instagram Dalam Meningkatkan Citra Indonesia Di Luar Negeri (Pada Perwakilan RI di KBRI Doha, Qatar) - Cut Intan Fadhillah; Tita Melia Milyane (Universitas Telkom, 2024)
This research aims to elucidate the implementation of Digital Public Relations (DPR) practices through the Instagram socialmedia platform conducted by the Embassy of the Republic of Indonesia (KBRI) in Doha, Qatar, with a focus on enhancingIndonesia’s international image. A nation’s image plays a pivotal role in influencing global perceptions and opinions aboutthe country. In the digital age, social media has emerged as a potent tool for shaping public views through compelling visualcontent and narratives.Employing a descriptive approach, this study utilizes qualitative data gathered from direct observations of KBRI Doha’s Instagram account and content analysis of posted material. The theoretical framework encompassesDPR concepts, the nation’s image, and the strategic use of social media as a communication tool. The collected data iscomprehensively analyzed to depict how KBRI Doha employs DPR practices through Instagram. The research findingsreveal that KBRI Doha has effectively employed DPR strategies through the Instagram platform by designing informativeand engaging content showcasing Indonesia’s cultural richness, economic potential, and innovative accomplishments. Thiscontent is curated with a consistent narrative guide, focusing on enhancing the positive image of Indonesia. Additionally,KBRI Doha actively engages with its followers, responding to inquiries and comments, thereby fostering direct dialogueswith its audience.